Prediction of the Remaining Service Life of Reinforced Concrete Structures - I. A. Terekhov; N. N. Trekin; E. N. Kodysh (Железобетонные конструкции)
The main indicators of durability, which characterize the time of operation of the structure before the onset of an emergency condition, are the total service life and the remaining service life, the determination of which allows a more reasonable approach to the issue of planning current or major repairs in the building. The most common engineering techniques that allow predicting the remaining service life for reinforced concrete structures are considered: according to standard terms and analogous objects, according to external signs, based on changes in reserve coefficients and strength criteria. Their modifications are given for a number of techniques. Based on the results of the analysis of the methods, their main advantages and disadvantages were established. As a proposal to improve the existing approaches, a methodology is proposed in which the interval between visual examinations is taken for the remaining period of operation.